Bayesian machine learning identifies precipitation as a key predictor in alpine soil carbon spatial structuring - Zhaoqi Wang; Sheng Yu; Xiaotao Huang; Ting Zhou; Haichen Zhang; Yangyang Liu; Guiling Wu; Kai Zheng; Mingxue Xiang; Tao Ma; Dan Liu; Yongkang Lu (Soil and Tillage Research, 2026)

Construction of 3D printed self-supporting electrode for efficient electrochemical lithium recovery from brine - Muyao He; Guiling Luo; Li Zhang; Jun Gu; Tongyu Wu; Xiaoxiao Yu; Minmeng Tang; Xiao Zhang; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2026)

Baculovirus manipulation of nutrient-based host choice via an infection responsive olfactory receptor in Spodoptera exigua - Zaiyuan Li; Xin Gao; Qihong Ma; Lianhai Fu; Changyou Li; Yan Shi; Jie Li; Qianlong Yu; Guiling Zheng; Chunhong Yang; Fanghao Wan; Wanqiang Qian; et al. (Pesticide Biochemistry and Physiology, 2026)

Covalently bonded amino-functionalized ZIF-8 on Cu2O for photocatalytic reduction of low-concentration CO2 - Jinke Li; Zhenbo Zhang; Guiling Liu; Hao Shi; Jingru Wang; Jiayi Wan; Tong Bian; Huijun Yu (Chemical Engineering Journal, 2026)

Responses of June Precipitation in Eastern China to Late Spring Soil Temperature Anomaly over the Qinghai–Xizang Plateau: Results from a Regional Climate Model - Wenchao Wang; Miao Yu; Yongkang Xue; Jianping Tang; Weiguang Liu; Guiling Wang; Jie Zhang; Hong Wu (Journal of Meteorological Research, 2025)

Synergistic effects of matrix metalloproteinases on the degradation of collagen in abalone (Haliotis discus hannai) - Yu-Lei Chen; Le-Le Su; Hua Liu; Tian-Bo Zhang; Guiling Li; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2025)

Constraints of hydrochemical and geological controls in deep-circulation geothermal systems: Insights from Chengde, Dehua, and Tashkorgan geothermal fields in China - Xiao Wang; Guiling Wang; Haonan Gan; Yu Zhang; Zhijuan Gao (Geothermics, 2025)

Refining water and carbon fluxes modeling in terrestrial ecosystems via plant hydraulics integration - Shanshan Sun; Lingcheng Li; Zong-Liang Yang; Guiling Wang; Nate G. McDowell; Ashley M. Matheny; Jian Wu; Shiqin Xu; Hui Zheng; Miao Yu; Dagang Wang (Agricultural and Forest Meteorology, 2024)

Regional climate model intercomparison over the Tibetan Plateau in the GEWEX/LS4P Phase I - Jianping Tang; Yongkang Xue; Mengyuan Long; Mengnan Ma; Xin-Zhong Liang; Shiori Sugimoto; Kun Yang; Zhenming Ji; Jinkyu Hong; Jeongwon Kim; Haoran Xu; Xu Zhou; et al. (Climate Dynamics, 2024)

Urban rainfall-runoff flooding response for development activities in new urbanized areas based on a novel distributed coupled model - Donglai Li; Jingming Hou; Qingshi Zhou; Jiahao Lyu; Zhanpeng Pan; Tian Wang; Xueliang Sun; Guiling Yu; Junyan Tang (Urban Climate, 2023)

3D-printed titanium-based ionic sieve monolithic adsorbent for selective lithium recovery from salt lakes - Jiangtao Yu; Jie Zhu; Guiling Luo; Linlin Chen; Xiaowei Li; Peng Cui; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2023)

A Responsive Feeding Questionnaire Based on Self-Determination Theory for Caregivers of Chinese Toddlers - Yan Liu; Guiling Yu; Zhihui Li; Yan Kong; Rui Yang; Chunlan Yin; Xiaodi Sun (Journal of Nutrition Education and Behavior, 2023)

Preparation of high hydrophilic H2TiO3 ion sieve for lithium recovery from liquid lithium resources - Jing Sun; Xiaowei Li; Yuhong Huang; Guiling Luo; Duanjian Tao; Jiangtao Yu; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2023)

Joint toxic effects of thiamethoxam and flusilazole on the adult worker honey bees (Apis mellifera L.) - Dou Wang; Lu Lv; Zhongwen Gao; Yu-Cheng Zhu; Hongbiao Weng; Guiling Yang; Yanhua Wang (Environmental Pollution, 2023)

Sensitivity of Typhoon Lingling (2019) simulations to horizontal mixing length and planetary boundary layer parameterizations - Siqi Chen; Feng Xu; Yu Zhang; Guiling Ye; Jianjun Xu; Chunlei Liu (Frontiers of Earth Science, 2022)

High-resolution distributions of O 2 / Ar on the northern slope of the South China Sea and estimates of net community production - Chuan Qin; Guiling Zhang; Wenjing Zheng; Yu Han; Sumei Liu (Ocean Science, 2021)
The dissolved oxygen-to-argon ratio (O2∕Ar) in the oceanic mixed layer has been widely used to estimate net community production (NCP), which is the difference between gross primary production and community respiration; it is a measure of the strength of the biological pump. In order to obtain the high-resolution distribution of NCP and improve our understanding of its regulating factors in the slope region of the northern South China Sea (SCS), we conducted continuous measurements of dissolved O2, Ar, and CO2 with membrane inlet mass spectrometry (MIMS) during two cruises in October 2014 and June 2015. An overall autotrophic condition was observed in the study region in both cruises with an average Δ(O2∕Ar) of 1.1 % ± 0.9 % in October 2014 and 2.7 % ± 2.8 % in June 2015. NCP was on average 11.5 ± 8.7 mmol C m−2 d−1 in October 2014 and 11.6 ± 12.7 mmol C m−2 d−1 in June 2015. Correlations between dissolved inorganic nitrogen (DIN), Δ(O2∕Ar), and NCP were observed in both cruises, indicating that NCP is subject to the nitrogen limitation in the study region. In June 2015, we observed a rapid response of the ecosystem to the episodic nutrient supply induced by eddies. Eddy-entrained shelf water intrusion, which supplied large amounts of terrigenous nitrogen to the study region, promoted NCP in the study region by potentially more than threefold. In addition, upwelling brought large uncertainties to the estimation of NCP in the core region of the cold eddy (cyclone) in June 2015. The deep euphotic depth in the SCS and the absence of correlation between NCP and the average photosynthetically available radiation (PAR) in the mixed layer in the autumn indicate that light availability may not be a significant limitation on NCP in the SCS. This study helps us to understand the carbon cycle in the highly dynamic shelf system.

Projecting the future vegetation–climate system over East Asia and its RCP-dependence - Weiguang Liu; Guiling Wang; Miao Yu; Haishan Chen; Yelin Jiang; Meijian Yang; Ying Shi (Climate Dynamics, 2020)

Potential climate effect of mineral aerosols over West Africa: Part II—contribution of dust and land cover to future climate change - Zhenming Ji; Guiling Wang; Miao Yu; Jeremy S. Pal (Climate Dynamics, 2018)

Combined toxicity of imidacloprid and three insecticides to the earthworm, Eisenia fetida (Annelida, Oligochaeta) - Tao Cang; Dejiang Dai; Guiling Yang; Yijun Yu; Lu Lv; Leiming Cai; Qiang Wang; Yanhua Wang (Environmental Science and Pollution Research, 2017)

Individual and mixture effects of five agricultural pesticides on zebrafish (Danio rerio) larvae - Yanhua Wang; Guiling Yang; Dejiang Dai; Zhenlan Xu; Leiming Cai; Qiang Wang; Yijun Yu (Environmental Science and Pollution Research, 2017)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Modeling the potential contribution of land cover changes to the late twentieth century Sahel drought using a regional climate model: impact of lateral boundary conditions - Guiling Wang; Miao Yu; Yongkang Xue (Climate Dynamics, 2016)

Identification and characterization of a novel NAC-like gene in chrysanthemum (Dendranthema lavandulifolium) - Yanfang Yang; Kai Zhu; Jian Wu; Liqing Liu; Guiling Sun; Yanbiao He; Fadi Chen; Deyue Yu (Plant Cell Reports, 2016)

Effects of vegetation feedback on future climate change over West Africa - Miao Yu; Guiling Wang; Jeremy S. Pal (Climate Dynamics, 2016)

Potential climate effect of mineral aerosols over West Africa. Part I: model validation and contemporary climate evaluation - Zhenming Ji; Guiling Wang; Jeremy S. Pal; Miao Yu (Climate Dynamics, 2016)

On the development of a coupled regional climate–vegetation model RCM–CLM–CN–DV and its validation in Tropical Africa - Guiling Wang; Miao Yu; Jeremy S. Pal; Rui Mei; Gordon B. Bonan; Samuel Levis; Peter E. Thornton (Climate Dynamics, 2016)

Potential impact of climate change on cereal crop yield in West Africa - Kazi Farzan Ahmed; Guiling Wang; Miao Yu; Jawoo Koo; Liangzhi You (Climatic Change, 2015)

Impact of climate change on hydrological extremes in the Yangtze River Basin, China - Huanghe Gu; Zhongbo Yu; Guiling Wang; Jigan Wang; Qin Ju; Chuanguo Yang; Chuanhao Fan (Stochastic Environmental Research and Risk Assessment, 2015)

Future changes of the terrestrial ecosystem based on a dynamic vegetation model driven with RCP8.5 climate projections from 19 GCMs - Miao Yu; Guiling Wang; Dana Parr; Kazi Farzan Ahmed (Climatic Change, 2014)

Polycyclic aromatic hydrocarbons in urban soils of Hangzhou: status, distribution, sources, and potential risk - Guoguang Yu; Zhiheng Zhang; Guiling Yang; Weiran Zheng; Lihong Xu; Zheng Cai (Environmental Monitoring and Assessment, 2014)

Impacts of bias correction of lateral boundary conditions on regional climate projections in West Africa - Miao Yu; Guiling Wang (Climate Dynamics, 2014)

Assessing future climate changes and extreme indicators in east and south Asia using the RegCM4 regional climate model - Huanghe Gu; Guiling Wang; Zhongbo Yu; Rui Mei (Climatic Change, 2012)

Integrating miRNA and mRNA expression profiles in response to heat stress-induced injury in rat small intestine - Jin Yu; Fenghua Liu; Peng Yin; Xiaoyu Zhu; Guiling Cheng; Nin Wang; An Lu; Weili Luan; Nuowei Zhang; Jiefeng Li; Kaijun Guo; Yulong Yin; et al. (Functional & Integrative Genomics, 2011)